2013
DOI: 10.1002/cphc.201300435
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Dynamics of a Radical Ion Pair in Micro‐Heterogeneous Binary Solvents: A Semi‐Quantitative Study Utilizing MARY Line‐Broadening Experiments

Abstract: This work aims at elucidating the mechanism of solvation of a radical ion pair (RIP) in a micro-heterogeneous binary solvent mixture using magnetically affected reaction yield (MARY) spectroscopy. For the exciplex-forming 9,10-dimethylanthracene/N,N-dimethylaniline system a comparative, composition-dependent MARY line-broadening study is undertaken in a heterogeneous (toluene/dimethylsulfoxide) and a quasi-homogenous (propyl acetate/butyronitrile) solvent mixture. The half-saturation field extrapolated to zero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…We observe that for n = 8 and 10, the B 1/2 -values are markedly larger than the corresponding value for the free fluorophore–quencher-pair DMAnt/DMA in the limit of low donor concentration ( B 1/2 = 5.3 mT). 5,6 This can be attributed to a reduced lifetime of the radical pair and/or singlet–triplet dephasing. In fact, the lifetime effect has been suggested to lead to a broadening of the MARY lines in a study of the micro-heterogeneous solvation of the radical pair of DMAnt/DMA in DMSO/toluene mixtures, which likewise promote large MFEs by increasing the reencounter probability.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observe that for n = 8 and 10, the B 1/2 -values are markedly larger than the corresponding value for the free fluorophore–quencher-pair DMAnt/DMA in the limit of low donor concentration ( B 1/2 = 5.3 mT). 5,6 This can be attributed to a reduced lifetime of the radical pair and/or singlet–triplet dephasing. In fact, the lifetime effect has been suggested to lead to a broadening of the MARY lines in a study of the micro-heterogeneous solvation of the radical pair of DMAnt/DMA in DMSO/toluene mixtures, which likewise promote large MFEs by increasing the reencounter probability.…”
Section: Results and Discussionmentioning
confidence: 99%
“…6 Singlet–triplet dephasing is the consequence of the randomization of the S/T-coherences by a time-varying J ( r ) as caused by the molecular motion. 5,6,47 Given that for n ≥ 8, no spectral fingerprints of an average exchange coupling are revealed in Figure 5, the picture of brief random encounters with large exchange coupling, interrupted by comparably long stretches of “free” evolution, emerges. We note again that the exchange interaction decays exponentially with the distance between two radicals.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, the singlet RIP concentration can be detected through the emission of the exciplex, which is produced by singlet RIP cage recombination (see Scheme 1b). 19,20,2933 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, using magnetic-field-affected-reaction-yield (MARY) line broadening measurements, the B 1/2 values were found to vary strongly with the solvent composition in microheterogeneous solvents. 19,20 Solvent mixtures composed of toluene (TO) and dimethyl sulfoxide (DMSO) have been studied in detail. 15,34 Studies of the magnetic isotope effect revealed no direct transfer of spin density on solvent molecules.…”
Section: Introductionmentioning
confidence: 99%